What About Platelet Counts in Clozapine Users? - Atmaca, Murad; Kilic, Faruk; Temizkan, Abdulgani; Ustundag, Bilal (Bentham Science Publ Ltd, 2013)
Objective: In this retrospective study, we aimed to evaluate platelet changes in patients taking clozapine for a variety of psychiatric disorders and hypothesized that there would be any changes in the course of the treatment. Methods: Diagnoses were based on Diagnostic and Statistical Manual of Mental Disorders 4 th edition. Forty-three patients, with the mean age of 36.23 +/- 6.35 years were included into final analysis. Morning venous blood samples were used for platelet counts. Correlation analyses were performed between platelet counts and clozapine doses. Results: Paired t test did not reveal a significant change in platelet counts at the end visit compared to those of first assessment (p>0.05). Seven (17.9%) of 39 patients had platelet count below 180000 per cubic millimeter at least one time during their clozapine use. In five of these patients, the platelet count returned to a level above 180000 per cubic millimeter, without any dose change or other interventions. On the other hand, as for the issue of increased platelet count, results demonstrated that seven (17.9%) had platelet count above 400000 per cubic millimeter at least one time during clozapine use. Conclusion: The present investigation revealed that platelet changes beyond WBC changes should be taken into consideration when using clozapine. Clinicians should be aware of the deviations from absolute threshold values.
Keywords: Platelet; clozapine; WBC; retrospective; side effect